Effects of Pergolide Mesylate on Plasma Adrenocorticotropic Hormone Concentration in Horses with Pituitary Pars Intermedia Dysfunction. (9th September 2013) - Rendle, D.I.; Taylor, E.; Duz, M.; Parkin, T.D.; Copas, V.E.N.; Durham, A.E.
Abstract : Aims: Pituitary pars intermedia dysfunction (PPID) is a common degenerative neuropathy of horses associated with ageing. Pergolide mesylate (pergolide) is the only licensed treatment for PPID in the UK; however, published evidence of its efficacy is limited to small case series and anecdotal reports. This study evaluated adrenocorticotropic hormone (ACTH) responses in horses treated with pergolide and investigated factors that may influence response to treatment. Methods: A retrospective review of submissions to The Liphook Equine Hospital Laboratory was performed from January 2007 to December 2012 and cases in which ACTH concentration was measured before and after instigation of pergolide treatment were identified. Data were analysed using Rv.2.15 software (R Development Core Team). Improvement was defined as a reduction of ACTH concentration of ≥75%, or a return of ACTH concentration to within seasonally adjusted reference intervals. Results: A total of 2122 cases satisfied the inclusion criteria. Improvement was identified in 54.8% of horses at the first follow‐up assessment; however, ACTH concentration returned to within reference intervals in only 28%. Equids with a higher ACTH concentration pretreatment were more likely to improve (odds ratio [OR] 1.01, 95% confidence intervals [CI] 1.00–1.02; P = 0.027), but less likely to return to within the reference interval (OR 0.97; 95% CI 0.96–0.98; P<0.001). Older equids were significantly less likely to improve (OR 0.56, 95% CI 0.46–0.67; P<0.001). Improvement was more likely after a cumulative dose of 50 mg (OR 1.59, 95% CI 1.10–2.29; P = 0.013) and duration of treatment was positively associated with treatment response (P = 0.039). A daily dose >0.5 μg/kg bwt was less likely to be associated with a reduction in ACTH concentration (OR 0.86, 95% CI 0.77–0.96; P = 0.009). Native breeds, mini and draught horses were more likely to return to the reference range than other breeds (OR 1.6, 95% CI 1.24–2.07; P<0.001). Neither gender nor season were associated with response to treatment. Conclusions and practical significance: Pergolide is an effective means of reducing ACTH concentration in equids with PPID. Ethical animal research: Not required by this Congress: retrospective clinical study.Sources of funding: None.Competing interests: Rendle and Durham have acted as paid speakers and consultants for Boehringer Ingelheim, manufacturers of Prascend, the licensed equine pergolide product.